2011
DOI: 10.4238/2011.november.29.8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in tetraploid switchgrass revealed by AFLP marker polymorphisms

Abstract: ABSTRACT. Switchgrass (Panicum virgatum) is a perennial warmseason grass native to North America that has been identified as a dedicated cellulosic biofuel crop. We quantified genetic diversity in tetraploid switchgrass germplasm collected at Oklahoma State University and characterized genetic relatedness among the collections from distinct regions. Fifty-six tetraploid accessions, including seven upland and 49 lowland genotypes from throughout the US, were examined. The amplified fragment length polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
3
15
1
1
Order By: Relevance
“…The UPGMA cluster and PCA analysis demonstrated that 134 genotypes could be clearly divided into two groups (Figs. 1 and 4), and the lowland and upland germplasm clusters were almost completely separated, which was consistent with the results of several other switchgrass studies [41, 55, 56]. For the UPGMA cluster analysis, the first group only included lowland ecotypes, while the second group contained upland ecotypes and could be further classified into two subgroups.…”
Section: Resultssupporting
confidence: 89%
“…The UPGMA cluster and PCA analysis demonstrated that 134 genotypes could be clearly divided into two groups (Figs. 1 and 4), and the lowland and upland germplasm clusters were almost completely separated, which was consistent with the results of several other switchgrass studies [41, 55, 56]. For the UPGMA cluster analysis, the first group only included lowland ecotypes, while the second group contained upland ecotypes and could be further classified into two subgroups.…”
Section: Resultssupporting
confidence: 89%
“…The least mean genetic similarity was observed between 'Kanlow' and the MME natural populations (0.635) while the highest was observed, as expected, between 'Alamo' populations collected at Vonore and Alcoa (0.936; Table 4). Similar genetic similarity coefficients ranging from 0.73 to 0.95 were observed while assessing genetic diversity in 56 accessions of tetraploid switchgrass (Todd et al 2011). In our study, the total mean genetic similarity among all switchgrass populations was 0.775, which is comparable to the mean genetic similarity of 0.813 observed in cultivated switchgrass accessions (Huang et al 2011).…”
Section: Resultssupporting
confidence: 71%
“…The study presented here offers important information on the genetic diversity and structure of natural and agronomic switchgrass populations and concurs with previous studies in genebank accessions, based on morphological, ploidy level and different molecular markers used (Cortese et al 2010;Huang et al 2011;Todd et al 2011;). Our study highlighted that: (1) these switchgrass populations contain a high level of genetic diversity, (2) the agronomic and natural populations we studied had same ploidy levels, (3) the populations are differentiated genetically, and (4) the diversity of natural populations is comparable to the agronomic populations.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations